Correction to: Evaluation After Cochlear Implant Surgery: Correlation of Clinical Outcome and Imaging Findings using Flat-detector CT (Clinical Neuroradiology, (2021), 31, 2, (367-372), 10.1007/s00062-020-00922-1) - Stock, Annika; Bozzato, Victoria; Kloska, Stephan; Bozzato, Alessandro; Hoppe, Ulrich; Hornung, Joachim; Dörfler, Arnd; Struffert, Tobias (Clinical Neuroradiology, 2021)
The article “Evaluation After Cochlear Implant Surgery” written by Annika Stock, Victoria Bozzato, Stephan P. Kloska, Alessandro Bozzato, Ulrich Hoppe, Joachim Hornung, Arnd Dörfler and Tobias Struffert was originally published Online First without Open Access. After publication in volume 31, issue 2, page 367–372 the authors decided to opt for Open Choice and to make the article an Open Access publication. Therefore, the copyright of the article has been changed to © The Author(s) 2020 and the article is forthwith distributed under the terms of the Creative Commons Attribution 4.0 International License, which permits use, sharing, adaptation, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons licence, and indicate if changes were made.
CRIS-Team Scopus Importer:2021-09-10